Team Dynamics in a Hybrid Work Environment: Effective Strategies for Enhancing Employee Performance and Well-being - Rahmatullah, Reska; Hari Edy Wibowo, Agoes; Mustaqim, M (Jurnal Informatika Ekonomi Bisnis, 2024)
This study investigates the intricate relationships among team dynamics, employee performance, and well-being in the context of a hybrid work environment, with a specific focus on PT Semen Baturaja (Persero) Tbk. Utilizing path analysis, the study explores both direct and indirect effects to unveil the dynamics shaping organizational practices related to hybrid work. The research reveals a significant direct impact of individual employee performance on both team dynamics and the establishment of a hybrid work environment. Team dynamics are identified as a crucial mediator, emphasizing their pivotal role in translating individual contributions into organizational strategies for hybrid work adaptation. However, the study finds that the direct influence of employee well-being on team dynamics and subsequently on the hybrid work environment may not be statistically significant. These findings offer nuanced insights for organizations aiming to optimize their work environment, suggesting tailored strategies to leverage team dynamics and individual performance for successful hybrid work implementation while considering the multifaceted nature of employee well-being.